Intimate partner violence and contraceptive use among married women in Nepal. Issue 3 (27th June 2019) - Acharya, Ajay; Weissman, Amy; Thapa, Basant; Chen, Mario
Abstract: Objective: To examine relationships between lifetime experience of intimate partner violence (IPV), and current contraceptive use and method among married women of reproductive age in Nepal. Methods: A cross‐sectional analysis of 2016 Nepal Demographic Health Survey data on contraceptive use and IPV experience among ever‐married women of reproductive age. Weighted percentages were reported and multinomial logistic regression was used to assess associations between IPV (physical, sexual, emotional, or any form) and contraception use (modern reversible, sterilization, or traditional). Results: Among 3562 women who responded to the violence module, 26% reported experiencing any form (physical, sexual or emotional) of IPV in their lifetime. Lifetime exposure to any form of IPV was associated with sterilization (adjusted odds ratio [aOR], 1.50; 95% confidence interval [CI], 1.12–2.00) and lifetime exposure to physical violence only was significantly associated with having been sterilized (aOR, 1.59; 95% CI, 1.17–2.16). Conclusion: Experience of violence, particularly physical violence, was found to be associated with sterilization in Nepal. Research is needed to understand the causes of this association, and the decision‐making power dynamics related to contraceptive use, husbands' attitudes toward sterilization, and the reasons why sterilization—relative to other contraceptive options—was the contraceptive method of choice. Abstract : Cross‐sectional analysis of Nepalese demographic and health survey data showed an association between lifetime experience of physical violence and sterilization among married women.